Introduction of Photolatent Bases for Locally Controlling Dynamic Exchange Reactions in Thermo‐Activated Vitrimers. Issue 26 (19th May 2021) - Reisinger, David; Kaiser, Simon; Rossegger, Elisabeth; Alabiso, Walter; Rieger, Bernhard; Schlögl, Sandra
Abstract: Vitrimers exhibit a covalently crosslinked network structure, as is characteristic of classic thermosetting polymers. However, they are capable of rearranging their network topology by thermo‐activated associative exchange reactions when the topology freezing transition temperature (Tv ) is exceeded. Despite the vast number of developed vitrimers, there is a serious lack of methods that enable a (spatially) controlled onset of these rearrangement reactions above Tv . Herein, we highlight the localized release of the efficient transesterification catalyst 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) by the UV‐induced cleavage of a photolatent base within a covalently crosslinked thiol–epoxy network. Demonstrated with stress relaxation measurements conducted well above the network's Tv, only the controlled release of TBD facilitates the immediate onset of transesterification in terms of a viscoelastic flow. Moreover, the spatially resolved UV‐mediated photoactivation of vitrimeric properties is confirmed by permanent shape changes induced locally in the material. Abstract : Vitrimers are covalently crosslinked polymers capable of rearranging their network topology through thermo‐activated associative exchange reactions. However, a locally controlled onset of these rearrangement reactions at elevated temperatures is a major challenge. A fundamental concept is demonstrated that enables controlled and, moreover, spatially resolved topology rearrangements triggerable by UV irradiation.